Vegetative Response of Cocoa Seedlings (Theobroma cacao L.) to Nitrophenol Compound Concentration and NPK Fertilizer Dose - Kusmiati; Eko Sutrisno; Sischa Febriani Yamesa Away; Putri Chairunnisa (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Cocoa is a vital plantation commodity in Indonesia, but its productivity is hindered by suboptimal seedling quality. This study aimed to evaluate the vegetative growth response of cocoa seedlings to various combinations of nitrophenol compound concentrations and NPK fertilizer doses, and to identify the optimal treatment combination. The experiment was conducted at the Experimental Garden of the Faculty of Agriculture, Pasir Pengaraian University, Riau, from June to October 2025, using a Randomized Complete Block Design (RCBD) with a factorial arrangement. The first factor was the concentration of nitrophenol compounds (0, 1.5, 3.0, and 4.5 ml/L), and the second factor was the NPK fertilizer dose (0, 5, and 10 g per polybag). The parameters measured included plant height, stem diameter, leaf number, root volume, and dry weight. Data were statistically analyzed using an F-test (ANOVA) at the 5% significance level with PKBT-STAT 3.2, followed by the Honestly Significant Difference (HSD) test at the 5% level. The results indicated a highly significant interaction (P < 0.01) between nitrophenol compounds and NPK fertilizer on all measured parameters. The combination of 4.5 ml/L nitrophenol compounds and 10 g/polybag NPK fertilizer produced the best results, with a plant height of 46.00 cm, 17 leaves, a stem diameter of 0.69 cm, a root volume of 6.50 ml, and a dry weight of 4.38 g. These findings demonstrate that increasing both the concentration of the nitrophenol compound and the fertilizer dose synergistically enhances the vigor and quality of cocoa seedlings.